Inhibitory effects of Jasminum grandiflorum L. essential oil on lipopolysaccharide-induced microglia activation-integrated characteristic analysis of volatile compounds, network pharmacology, and BV-2 cell - Lu, Jingya; Zeng, Xiaoyan; Feng, Yanping; Li, Siyi; Wang, Yun; Liu, Youlin; Chen, Feilong; Guan, Zhenfeng; Chen, Tiantian; Wei, Fenghuan (Frontiers in Pharmacology, 2023)
Neuroinflammation is considered to have a prominent role in the pathogenesis of Alzheimer’s disease (AD). Microglia are the resident macrophages of the central nervous system, and modulating microglia activation is a promising strategy to prevent AD. Essential oil of Jasminum grandiflorum L. flowers is commonly used in folk medicine for the relief of mental pressure and disorders, and analyzing the volatile compound profiles and evaluating the inhibitory effects of J. grandiflorum L. essential oil (JGEO) on the excessive activation of microglia are valuable for its application. This study aims to explore the potential active compounds in JGEO for treating AD by inhibiting microglia activation-integrated network pharmacology, molecular docking, and the microglia model. A headspace solid-phase microextraction combined with the gas chromatography–mass spectrometry procedure was used to analyze the volatile characteristics of the compounds in J. grandiflorum L. flowers at 50°C, 70°C, 90°C, and 100°C for 50 min, respectively. A network pharmacological analysis and molecular docking were used to predict the key compounds, key targets, and binding energies based on the detected compounds in JGEO. In the lipopolysaccharide (LPS)-induced BV-2 cell model, the cells were treated with 100 ng/mL of LPS and JGEO at 7.5, 15.0, and 30 μg/mL, and then, the morphological changes, the production of nitric oxide (NO) and reactive oxygen species, and the expressions of tumor necrosis factor-α, interleukin-1β, and ionized calcium-binding adapter molecule 1 of BV-2 cells were analyzed. A total of 34 compounds with significantly different volatilities were identified. α-Hexylcinnamaldehyde, nerolidol, hexahydrofarnesyl acetone, dodecanal, and decanal were predicted as the top five key compounds, and SRC, EGFR, VEGFA, HSP90AA1, and ESR1 were the top five key targets. In addition, the binding energies between them were less than −3.9 kcal/mol. BV-2 cells were activated by LPS with morphological changes, and JGEO not only could clearly reverse the changes but also significantly inhibited the production of NO and reactive oxygen species and suppressed the expressions of tumor necrosis factor-α, interleukin-1β, and ionized calcium-binding adapter molecule 1. The findings indicate that JGEO could inhibit the overactivation of microglia characterized by decreasing the neuroinflammatory and oxidative stress responses through the multi-compound and multi-target action modes, which support the traditional use of JGEO in treating neuroinflammation-related disorders.